The Tale of Two Urban School Principals: Barriers, Supports, and Rewards - Acton, Karen S. (Alberta Journal of Educational Research, 2018)
Urban schools in high-poverty communities face unique challenges. It is often the school principal who is tasked with addressing achievement gaps, low scores and students with high needs. Despite the importance and the difficulties of their role, the voices of many of these dedicated leaders are not often heard. This narrative inquiry shares the insights of two elementary principals in urban schools who recount the barriers, supports and rewards of their role. Using moral leadership as a theoretical framework, the findings of this study include a call for school boards to consider carefully the qualities and passions of their leaders when assigning principals to urban schools. Keywords: principal, moral leadership, high-poverty, urban schools, narrative inquiry Les écoles en milieux urbains avec des taux élevés de pauvreté font face à des défis uniques. Il revient souvent aux directeurs d’école de répondre aux écarts en matière de rendement, aux faibles résultats et aux élèves ayant des besoins élevés. Malgré l’importance et les difficultés de leur rôle, les voix de plusieurs de ces leaders dévoués ne se font pas souvent entendre. Cette enquête narrative présente les perspectives de deux directeurs d’écoles primaires urbaines qui racontent les obstacles, les supports et les récompenses qui les accompagnent dans leur rôle. Reposant sur le leadership moral comme cadre théorique, les résultats évoquent, entre autres, le besoin pour les conseils scolaires d’examiner soigneusement les qualités et les passions de leurs leaders lors de l’affectation des directeurs dans les écoles urbaines. Mots clés : directeur, leadership moral, taux élevé de pauvreté, écoles urbaines, enquête narrative